Characterization of the natural hybrid between two wild rice species (Oryza minuta Presl. and Oryza officinalis Well ex. Watt) - Sana, E. A. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2003)
The sterile wild rice population was compared with the parental species based on morphology cytology, isozyme patterns and simple sequence repeat (SSR) Ioci. This population is believed to be a natural hybrid of O. officinalis and O. minuta. Characterization also included the two progeny plants (designated as F2 officinalis and F2 minuta based on morphology) produced from two seeds set by the putative hybrid.